Extração, purificação e imobilização de lipases vegetais destinadas à síntese de biodiesel e ésteres - Vescovi, Vinicius (2012)
Lipases (triacyl-glycerol-hydrolases) are enzymes that catalyze hydrolysis, esterification and transesterification reactions. Lipase can be obtained from animals, microbial and vegetable sources. Nowadays, commercial lipases are majority produced from microbial sources. The use of these enzymes in industrial scale is still limited because of its high cost of production, favoring then, the search for new sources of lipases. This work aimed the utilization of oilseeds as lipase sources, aiming its use in the synthesis of fatty esters and in the hydrolysis of vegetable oils. To achieve this goal, the protein content of seeds of sunflower, castor bean and soybean was solubilized in buffered medium. The oilseeds were crushed in the presence of sodium phosphate buffer pH 7.0 (50 mM), followed by 11 hconstant stirring at room temperature. Under these conditions, the average productivities were ca. 237, 100 and 81 U/g of dried seeds. The solids were withdrawal from the crude extract by filtration, followed by centrifugation. The clarified crude extract was purified by ultrafiltration in 100 kDa cut-off polypropylene membrane. This procedure allows an activity recovery of 40, 35 and 11% for soybean, sunflower and castor bean, respectively. The purified lipases from soybean, sunflower and castor bean seeds were immobilized on hydrophobic support (silica-octyl) by interfacial adsorption, yielding biocatalysts with recovered activities of 683%, 413% and 1494%, respectively. SDS-PAGE electrophoresis and activity assays during the immobilization of the purified lipases on silica-octil suggested the presence of two lipase isoforms with molecular weights around of 20 and 30 kDa. Soluble soybean lipase exhibited optimum pH and temperature for hydrolysis of olive oil around 8.0 and 47 °C, respectively, while for immobilized soybean lipase (derivative) were 6.0 and 57°C, respectively. The halflife of the immobilized lipase at 50oC and pH 7 was around 8 h. The synthesis of butyl butyrate at 40oC catalyzed by immobilized lipase yield a conversion of approximately 15% after 9 h of reaction. The productivity of lipases from soybean seeds can be increased by germination of the seeds for 12 h, followed by extraction at 25oC for 12 h with salt solution (sodium phosphate buffer pH 7.0) at 100 mM concentration, supplemented with 1% (m/v) Tris-HCl.